Family planning counselling on third postpartum visit and the stability as acceptors of postpartum family planning - Hasri Yulianti; Ignasensia Dua Mirong (Jurnal Kesehatan Ibu dan Anak, 2020)
Family planning services was an effort to reduce the Maternal Mortality Rate factors that is too young give birth under 21 years old, too old give birth over 35 years, too close birth spacing less than 2 years, and having too many children more than 2. A promotion and counseling about postpartum family planning are necessary to be carried out for mothers and their children, especially couples who are in a childbearing age to increase the achievement of postpartum family planning. The objective was to determine the effect of family planning counseling during the third postpartum visit toward the stability as acceptors of postpartum family planning. The type of study was analytic survey research with a cross sectional approach that was conducted at Sikumana Health Center in 2018. The numbers of samples were 54 people. The data were analyzed using chi-square with the Fisher Exact test. Result: The univariate result shown that most of respondent was 20-35 years old (88.9%), have been received family planning counselling (88.9%) but have not yet been family planning acceptors (34.6%). The result of Fishers exact correlation test p=0.047, OR= 1.714 it shows that there was a significant influence between family planning counseling on the 3rd visit during the postpartum period on the stability of being a family planning acceptor after childbirth delivery. There is an effect of family planning counseling on the stabilization of postpartum family planning acceptors.